Risk Assessment of Technology Change in Financial Sector - Lim, Qian Pink; Mohd Ridzuan, Darun (2014)
A review of current risk management practices among Internet banking providers is presented given the increasing breach of security incidents worldwide. In-depth analysis is performed using Internet banking guidelines issued by three central banks (Central Bank of Malaysia, Monetary Authority of Singapore and Hong Kong Monetary Authority). Three distinctive risks are identified (informational security, transactional and strategic risks) as the most relevant among the guidelines studied. These risks are then mapped against threats towards achieving bank’s goals using Sheehan’s Risk Based Approach to Strategy Execution framework. The likelihood and magnitude of each risk was evaluated based on different perspectives proposed in the strategy map. The analysis concludes that gradual migration towards internalisation of essential processes is central to improving internet banking security. Future research should aim to gather richer sources of information through interviews with banking personnel to gain better insight into risks and how they are managed.